2013
DOI: 10.1021/jp402530s
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Formation Mechanism of Boehmite with Different Morphology upon Surface Hydroxyls and Adsorption of Chloride Ions

Abstract: Identification of the key factors of morphology control in nanomaterial synthesis is important for mechanism understanding of the reactivity–structure relationship and rational design of crystals with desired morphology. Among others, the inorganic ions in solution were found to be a key factor in controlling the final morphology. To reveal the effect of inorganic ions, the boehmite with different morphologies influenced by chloride ions is studied by a combined experimental and computational approach. The qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 45 publications
1
54
0
Order By: Relevance
“…4. Considering recent findings [40], the exothermic nature of peak A1 was attributable to Cl À interaction with "MeOHAAl 5 hydroxyls along the (0 0 1) plane. The relative intensities of peaks A1, A2, and A3 were also consistent with the relative proportion of different hydroxyls for c-AlOOH and pointed to "MeOHAAl 6 (along the (1 0 0) plane) and "MeOHAAl 4 (along the (1 0 1) plane) hydroxyls as the most likely sites accounting for peaks A2 and A3 respectively [38].…”
Section: Enthalpy Of Phosphate Ligand Exchange and Its Effects On CL mentioning
confidence: 59%
See 4 more Smart Citations
“…4. Considering recent findings [40], the exothermic nature of peak A1 was attributable to Cl À interaction with "MeOHAAl 5 hydroxyls along the (0 0 1) plane. The relative intensities of peaks A1, A2, and A3 were also consistent with the relative proportion of different hydroxyls for c-AlOOH and pointed to "MeOHAAl 6 (along the (1 0 0) plane) and "MeOHAAl 4 (along the (1 0 1) plane) hydroxyls as the most likely sites accounting for peaks A2 and A3 respectively [38].…”
Section: Enthalpy Of Phosphate Ligand Exchange and Its Effects On CL mentioning
confidence: 59%
“…This favorability ranking is very much in-line with the relative basicity of the different hydroxyls and hence their tendency to exist in their protonated form under acidic conditions [38,40]. For example, Raybaud et al [38,40] from their DFT calculations found that the enthalpy of adsorption for NH 3 (a base) onto "MeOHAAl 5 , "MeOHAAl 6 and "MeOHAAl 4 hydroxyls was À34.3, À42.6 and À55.5 kJ mol À1 respectively-reflecting an increase in acidity (decrease in basicity) of the respective hydroxyls. Our favorability ranking also suggested that phosphate which was adsorbed to the most basic (least acidic) hydroxyls were the most susceptible to exchange by Cl À (and likely other simple anionic species).…”
Section: Enthalpy Of Phosphate Ligand Exchange and Its Effects On CL mentioning
confidence: 66%
See 3 more Smart Citations